1988
DOI: 10.1177/0887302x8800600201
|View full text |Cite
|
Sign up to set email alerts
|

Apparel Selection by Employed Women: A Typology of Information Search Patterns

Abstract: The purposes of this study were: 1) to identify segments of employed women purchasers of apparel who display different information search patterns; and 2) to examine the relationship between information search patterns and consumer, product, situational, and market characteristics. Data from a national random sample of 1034 employed women were analyzed. Using a Principal Components Factor Analysis of information search activities, five factors were extracted and labeled: Print-Oriented, Audio-Visual Oriented, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 7 publications
3
30
0
Order By: Relevance
“…Some research (Shim and Drake 1988;Rabolt and Drake 1984/85) has shown that demographic variables may in¯uence the fashion adoption process. The only demographic characteristic that differentiated leaders and followers was work status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some research (Shim and Drake 1988;Rabolt and Drake 1984/85) has shown that demographic variables may in¯uence the fashion adoption process. The only demographic characteristic that differentiated leaders and followers was work status.…”
Section: Discussionmentioning
confidence: 99%
“…Some research has also indicated that variables such as age, socio-economic status, income, occupation and education may in¯uence the fashion adoption process (Shim and Drake 1988;Rabolt and Drake 1984/5).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Research has indicated specific patterns of information search by individuals purchasing durable goods (Claxton, Fry, & Portis, 1974;Furse, Punj, & Stewart, 1984) as well as the use of distinct information search patterns by employed women when making apparel selections (Shim & Drake, 1988). Research has indicated specific patterns of information search by individuals purchasing durable goods (Claxton, Fry, & Portis, 1974;Furse, Punj, & Stewart, 1984) as well as the use of distinct information search patterns by employed women when making apparel selections (Shim & Drake, 1988).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The four-item version of the measure of impulsiveness, with high factor loadings on the scale was used in the current study. In this study, the dimension of shopping confidence developed by Shim and Drake (1988) was reflected as the level of confidence in a person when dealing with shopping for clothing or accessories and displaying for the presentable self. To identify a respondent's degree of agreement with the shopping confidence, this dimension was assessed based on the six items.…”
Section: Methodsmentioning
confidence: 99%